Al-Si casting alloy with good corrosion resistance in as-cast state and preparation method of Al-Si casting alloy
By adjusting the chemical composition and microstructure of the Al-Si casting alloy, the corrosion problem in the presence of chloride ions is solved, and the effect of improving corrosion resistance at low cost is achieved.
Patent Information
- Application Number
- CN202411552091.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
AI Technical Summary
The existing Al-Si cast alloys are prone to corrosion under the presence of chloride ions, and the cost of improving corrosion resistance of heat treatment and chemical methods is high, making it difficult to improve the corrosion resistance of their cast state at low cost.
By adjusting the chemical composition of the Al-Si casting alloy, including controlling the Si content between 3.0 and 5.5 wt%, adding Sr and rare earth elements to deteriorate the Si phase, making it appear in a fine granular or fibrous shape, reducing the grain boundary Si phase Quantity and continuity. At the same time, by adding micro-addition of Mn and Cr, the β-Fe phase is converted into α-Al(Fe,Mn,Cr)Si that is closer to the matrix potential, and Ti elements are added to refine the grains and improve the formation of the oxide film.
It effectively slows down the diffusion rate of corrosion, improves the corrosion resistance of Al-Si cast alloy in cast state, and reduces production costs.
Smart Images

Figure CN119392054A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of casting alloys, and in particular relates to an Al-Si casting alloy with good corrosion resistance in a cast state and a preparation method thereof. Background Art
[0002] With the continuous development of lightweight automobiles, aluminum alloys are increasingly used in automobiles. As the largest type of aluminum alloy used in automobiles, Al-Si casting alloys are used in drive systems, chassis, body and other systems. In different application scenarios, the performance requirements for Al-Si casting alloys are not the same. Compared with some stressed structural parts, some more functional parts do not have high requirements for material mechanical properties, but have high requirements for corrosion resistance.
[0003] Under normal temperature conditions, dense aluminum oxide will be produced on the surface of aluminum, so it has good corrosion resistance. However, in the presence of chloride ions, the aluminum oxide film is easily destroyed by chloride ions, resulting in local corrosion. Heat treatment is an important means to regulate the structure of Al-Si casting alloys and improve corrosion resistance, but heat treatment will increase production costs, and it is easy to cause deformation of castings and reduce the yield rate. In addition, chemical methods such as passivation and anodizing can also effectively improve corrosion resistance, but they will significantly increase the cost of castings.
[0004] Therefore, it is necessary to find low-cost methods to improve the corrosion resistance of Al-Si casting alloys in the cast state to promote their application in related parts.
[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0006] The purpose of the present invention is to provide an Al-Si casting alloy with good corrosion resistance in the cast state and a preparation method thereof. The Al-Si casting alloy of the present invention has excellent corrosion resistance and high application performance.
[0007] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0008] An Al-Si casting alloy with good corrosion resistance in the cast state, the chemical composition of which includes, by mass percentage, Si: 3.0-5.5wt%, Mg: 0.2-0.8wt%, Fe: ≤0.2wt%, Ti: 0.03-0.3wt%, Sr: 0.005-0.06wt%, RE: 0.02-0.5wt%, Mn: 0.05-0.4wt%, Cr: 0.01-0.3wt%, Cu: 0.05-0.2wt%, and the rest is Al and inevitable impurities.
[0009] In one or more embodiments of the present invention, in the element content of the Al-Si casting alloy, the ratio of the sum of the content of Mn and Cr to the content of Fe is 2-5.
[0010] In one or more embodiments of the present invention, the microstructure of the Al-Si casting alloy includes an α-Al matrix, a eutectic Si phase, a Fe-containing phase, a β-Mg2Si phase, and an Al4X3Si6 phase.
[0011] In one or more embodiments of the present invention, the α-Al matrix is dendritic and / or equiaxed, with an average grain size of 50 to 200 μm and a secondary dendrite arm spacing of 10 to 40 μm.
[0012] In one or more embodiments of the present invention, the volume fraction of the eutectic Si phase is 2-5%.
[0013] In one or more embodiments of the present invention, the eutectic Si phase is in the form of particles and fibers, with an average size of 1 to 3 μm.
[0014] In one or more embodiments of the present invention, the Fe-containing phase includes α-Al(Fe, Mn, Cr)Si phase, π-Al 18 Fe2Mg7Si 10 phase, β-Al9Fe2Si2 phase.
[0015] In one or more embodiments of the present invention, the average size of the Fe-containing phase is 2-10 μm.
[0016] In one or more embodiments of the present invention, the total amount of the Fe-containing phase is less than 1.2 vol.%.
[0017] In one or more embodiments of the present invention, the content of the β-Al9Fe2Si2 phase is less than 0.05 vol.%.
[0018] In one or more embodiments of the present invention, the Al4X3Si6 phase includes Al4Ce3Si6 phase and / or Al4La3Si6 phase.
[0019] In one or more embodiments of the present invention, the RE is cerium, lanthanum, or a combination of both.
[0020] Another specific embodiment of the present invention provides a technical solution as follows:
[0021] A method for preparing an Al-Si casting alloy having good corrosion resistance in a cast state comprises the following steps:
[0022] Place pure Al ingot and Al-Si master alloy in a melting furnace and heat to 750-800°C for melting;
[0023] The temperature of the smelting furnace is lowered to 740-780°C, Al-Ti master alloy, Al-Mn master alloy, Al-Cr master alloy, Al-RE master alloy and pure Cu agent are added into the smelting furnace for melting to obtain a melt, the melt is kept at 700-730°C, and then Mg blocks are added for melting and kept for a certain time;
[0024] Then, the Al-Sr master alloy is added into a smelting furnace for melting to obtain a molten material;
[0025] Then add 1.0-5.0‰ refining agent and 1.0-10.0‰ refiner of the mass of the molten material into the smelting furnace, stir and degas for 10-30 minutes, let it stand for 10-30 minutes, then slag and cast, and obtain Al-Si casting alloy with good corrosion resistance in the cast state.
[0026] In one or more embodiments of the present invention, the casting method includes gravity casting, high pressure casting, squeeze casting, low pressure casting, differential pressure casting and the like.
[0027] In one or more embodiments of the present invention, during the casting process, the cooling rate of the casting is greater than or equal to 2° C. / s.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention reduces the Si content and utilizes Sr and rare earth elements for modification, thereby reducing the amount and continuity of the grain boundary Si phase and changing the morphology of Si to make it in the form of fine particles or fibers, thereby slowing down the corrosion diffusion rate and improving the corrosion resistance.
[0030] (2) By adding rare earth elements (Ce / La), the size of the Fe phase can be refined. During the solidification process, the rare earth elements (Ce / La) will be concentrated near the Fe-containing phase, inhibiting its growth. At the same time, since the potential of the Ce and La-containing phase is lower than that of the aluminum matrix, it will not cause preferential corrosion of the aluminum matrix, thereby changing the corrosion behavior.
[0031] (3) By adding trace amounts of Mn and Cr, the β-Fe phase can be transformed into α-Al(Fe,Mn,Cr)Si, which is closer to the matrix potential, reducing the corrosion area. In addition, some Mn and Cu will be dissolved in the α-Al matrix, thereby increasing the potential of the α-Al matrix and slowing down the galvanic corrosion between the second phase at the grain boundary and the α-Al matrix.
[0032] (4) By adding Ti, the number of nucleation points in the α-Al matrix can be increased, grain refinement can be achieved, the number of grain boundaries can be increased, and the density of the second phase at the grain boundaries can be reduced, thereby preventing corrosion from spreading along the grain boundaries. At the same time, it is beneficial to increase the formation rate of the alloy oxide film, make the oxide film more complete, reduce defects, and enhance the corrosion resistance of the alloy. In addition, rare earth elements (RE) can also promote the nucleation of α-Al grains and inhibit the growth of α-Al after nucleation, thereby achieving the purpose of grain refinement and further improving corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is a metallographic morphology diagram of the casting structure of the Al-Si casting alloy in Example 1 of the present invention;
[0035] Figure 2 The casting structure scanning photo (a) and energy spectrum result (b) of the Al-Si casting alloy in Example 1 of the present invention;
[0036] Figure 3 This is a schematic diagram of the cross-sectional structure of the Al-Si casting alloy after 24 hours of intergranular corrosion in Example 1 of the present invention;
[0037] Figure 4 This is a schematic diagram of the cross-sectional structure of the Al-Si casting alloy after 24 hours of intergranular corrosion in Example 2 of the present invention;
[0038] Figure 5 This is a schematic diagram of the cross-sectional structure of the Al-Si casting alloy after intergranular corrosion for 24 hours in Comparative Example 1 of the present invention;
[0039] Figure 6 This is a schematic diagram of the cross-sectional structure of the Al-Si casting alloy in Comparative Example 2 of the present invention after 24 hours of intergranular corrosion. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0041] Under normal temperature conditions, the surface of aluminum will produce dense aluminum oxide, so it has good corrosion resistance, but in the presence of chloride ions, the aluminum oxide film is easily destroyed by chloride ions, resulting in local corrosion. For Al-Si casting alloys, the corrosion generally extends inward along the grain boundary eutectic structure area. The eutectic structure of Al-Si casting alloys is mainly composed of second phases such as eutectic α-Al, Si phase, β-Fe, and π-Fe. The potential of these second phases is generally higher than the α-Al matrix around them, resulting in the α-Al matrix being corroded preferentially. Among them, the potential difference between the Si phase and the α-Al matrix is the largest, but its corrosion current is small, so its effect on corrosion is relatively small, and the potential difference between β-Fe and the α-Al matrix is greater than the potential difference between π-Fe and the α-Al matrix, resulting in corrosion preferentially occurring near it during the corrosion process. The corrosion of Al-Si casting alloys is not only related to the type of second phase, but also closely related to the number, size, and morphology of the second phase. Therefore, the present invention reduces the potential difference between the second phase and the matrix by controlling the type, quantity, and morphology of the Fe phase, and slows down the corrosion rate.
[0042] Although the effect of Si on corrosion is relatively small, if it is continuously arranged along the grain boundaries in the form of plates or the like, it will cause corrosion to expand inward. In order to reduce the amount of Si phase at the grain boundaries and take into account the requirements of mechanical properties and casting performance, the present invention controls the Si content between 3 and 5.5wt%. In addition, the morphology of the Si phase will also affect the expansion of corrosion, so it is necessary to add Sr as a modifier to promote the modification of the Si phase, form fine granular or fibrous eutectic Si structure, and slow down the diffusion efficiency of corrosion. In order to ensure a good modification effect, the present invention controls the Sr content between 0.005 and 0.06wt%, and reduces the amount and continuity of the Si phase at the grain boundaries by reducing the Si content and the Sr modification effect.
[0043] In order to reduce the amount of β-Fe phase, on the one hand, it is necessary to reduce the Fe content and control its content below 0.2wt%, and at the same time, it is necessary to add other elements to modify it. The addition of Mn and Cr can transform the β-Fe phase into the α-Al(Mn,Cr,Fe)Si phase which is closer to the matrix potential, but the addition of Cr alone has no obvious effect on the transformation of the Fe phase, and excessive addition of Mn will increase the amount of Fe phase in the alloy and increase the size, which is not conducive to corrosion resistance and elongation. Therefore, the present invention adopts the means of synergistically adding Mn and Cr to transform the β-Fe phase with maximum control, avoiding the excessive addition of Mn element alone, so the Mn content is controlled between 0.05 and 0.4wt%, the Cr content is controlled between 0.01 and 0.3wt%, and the ratio of the sum of the Mn and Cr contents to the Fe content, i.e. (Mn+Cr) / Fe, is controlled between 2 and 5, at which time the β-Fe phase is basically eliminated.
[0044] Mg is the main strengthening element in aluminum alloy. Adding Mg to Al-Si alloy can form Mg2Si phase, which is pinned to the aluminum grain boundary to prevent the slip of dislocations and improve the tensile strength of the alloy. At the same time, Mg will also promote the formation of π-Fe phase, and the harm of π-Fe phase to corrosion resistance is far less than that of β-Fe phase. Therefore, increasing the Mg content appropriately will also help reduce the β-Fe phase. Considering the strengthening effect of Mg and the modification effect of Fe phase, the Mg content is controlled between 0.2 and 0.8wt%. In addition, the presence of rare earth elements Ce and La can refine the size of Fe phase and change its type and morphology. During the solidification process, rare earth elements will be concentrated near the Fe-containing phase to inhibit its growth. At the same time, since the potential of the Ce- and La-containing phases is lower than that of the aluminum matrix, it will not cause preferential corrosion of the aluminum matrix, thereby changing the corrosion behavior. Therefore, the total amount of Ce and La is controlled at 0.02 to 0.5wt%.
[0045] Increasing the potential of the matrix is also an important means to reduce the potential difference between the second phase at the grain boundary and the α-Al matrix. During the solidification process, part of the Mn and Cu will dissolve in the α-Al matrix, thereby increasing the potential of the α-Al matrix and slowing down the galvanic corrosion between the second phase at the grain boundary and the α-Al matrix. However, excessive Cu addition will lead to the formation of Al2Cu, which will deteriorate the corrosion resistance. Therefore, the Cu content is controlled between 0.05 and 0.2wt%.
[0046] The addition of Ti can increase the number of nucleation points in the α-Al matrix, achieve grain refinement, increase the grain boundary area, and then reduce the density of the second phase at the grain boundary, reduce the width of the eutectic structure, and hinder the corrosion from spreading along the grain boundary. At the same time, the tighter the grain arrangement, the more conducive it is to increase the formation speed of the alloy oxide film, make the oxide film more complete, reduce defects, and enhance the corrosion resistance of the alloy. Therefore, the Ti content is controlled between 0.03 and 0.3wt%. In addition, in addition to modifying the Fe-containing phase, rare earth elements can also promote the nucleation of α-Al grains and inhibit the growth of α-Al after nucleation, thereby achieving the purpose of grain refinement.
[0047] A specific embodiment of the present invention provides an Al-Si casting alloy with good corrosion resistance in the cast state, and its chemical composition includes, by mass percentage: Si 3.0-5.5wt%, Mg 0.2-0.8wt%, Fe≤0.2wt%, Ti 0.03-0.3wt%, Sr 0.005-0.06wt%, RE 0.02-0.5wt%, Mn 0.05-0.4wt%, Cr 0.01-0.3wt%, Cu 0.05-0.2wt%, and the rest is Al and unavoidable impurities.
[0048] Preferably, the ratio of the sum of the contents of Mn and Cr to the content of Fe, ie, (Mn+Cr) / Fe, is 2 to 5, which is beneficial to eliminating the β-Fe phase.
[0049] Furthermore, the microstructure of the Al-Si casting alloy includes an α-Al matrix, a eutectic Si phase, a Fe-containing phase, a β-Mg2Si phase, and an Al4X3Si6 phase.
[0050] Specifically, the α-Al matrix is dendritic and / or equiaxed, with an average grain size of 50 to 200 μm and a secondary dendrite arm spacing of 10 to 40 μm. The α-Al matrix is a supersaturated solid solution, including alloy elements such as Mn and Cu, which can slow down the galvanic corrosion between the grain boundary second phase and the α-Al matrix.
[0051] Specifically, the volume fraction of the eutectic Si phase is 2-5%, the morphology is granular and fibrous, and the average size is 1-3 μm.
[0052] Furthermore, the Fe-containing phase includes α-Al(Fe, Mn, Cr)Si phase, π-Al 18 Fe2Mg7Si 10 The average size of the Fe-containing phase is 2 to 10 μm, the total amount of the Fe-containing phase is controlled below 1.2 vol.%, and the content of the β-Al9Fe2Si2 phase is less than 0.05 vol.%.
[0053] Furthermore, RE is one or a combination of cerium and lanthanum. The addition of rare earth elements can modify the Fe-containing phase and achieve grain refinement.
[0054] Another specific embodiment of the present invention provides a method for preparing an Al-Si casting alloy having good corrosion resistance in a cast state, comprising the following steps:
[0055] Place pure Al ingot and Al-Si master alloy in a melting furnace and heat to 750-800°C for melting;
[0056] The temperature of the smelting furnace is lowered to 740-780°C, Al-Ti master alloy, Al-Mn master alloy, Al-Cr master alloy, Al-RE master alloy and pure Cu wire are added into the smelting furnace for melting to obtain a melt, the melt is kept at 700-730°C, and then Mg blocks are added for melting and kept for a certain time;
[0057] Then, the Al-Sr master alloy is added into a smelting furnace for melting to obtain a molten material;
[0058] Then add 1.0-5.0‰ refining agent and 1.0-10.0‰ refiner of the mass of the molten material into the smelting furnace, stir and degas for 10-30 minutes, let it stand for 10-30 minutes, then slag and cast, and obtain Al-Si casting alloy with good corrosion resistance in the cast state.
[0059] Specifically, the casting can be carried out by gravity casting, high pressure casting, squeeze casting, mortgage casting or differential pressure casting. During the casting process, the gradual cooling rate is greater than or equal to 2°C / s to ensure that the casting has good corrosion resistance.
[0060] The present invention is further described in detail below in conjunction with specific embodiments.
[0061] Example 1
[0062] The Al-Si casting alloy has good corrosion resistance in the cast state, and the components of the Al-Si casting alloy are, by mass percentage, as follows: Si: 4.6wt%; Mg: 0.34wt%; Fe: 0.08wt%; Ti: 0.22wt%; Sr: 0.02wt%; Ce: 0.05wt%; Mn: 0.10wt%; Cr: 0.09wt%; Cu: 0.06wt%, and the rest are Al and unavoidable impurities.
[0063] The preparation method of Al-Si casting alloy is as follows:
[0064] Place the raw materials of industrial pure Al ingot and Al-Si master alloy in a melting furnace and heat them to 790℃±10℃. After the raw materials in the melting furnace are melted, cool the melting furnace to 750℃±10℃.
[0065] Add Al-Ti master alloy, Al-Mn master alloy, Al-Cr master alloy, Al-Ce master alloy and Cu agent into the melting furnace until they are completely melted, then cool the melting furnace to 740℃±10℃, add Mg block, press it under the liquid surface until it is completely melted, and keep it warm for 5 minutes;
[0066] Add Al-Sr master alloy into a smelting furnace until it is completely melted to obtain a molten material, and control the amount of each raw material added so that the content of each component is as shown in the above formula;
[0067] Add 2‰ of the mass of the molten material to the smelting furnace with a solid refining agent (specifically Foseco Coveral78) and 5.0‰ of a refiner (specifically Shenzhen Xinxing Al-Ti5-B refiner), and use a rotating rotor to stir and degas for 20 minutes. After the degassing is completed, stand for 20 minutes and then skim the slag to obtain a refined metal melt;
[0068] When the temperature of the molten metal is at 740°C±10°C, the molten metal is poured into a steel mold preheated at 175°C±10°C to obtain a casting; wherein, during the casting process, the cooling rate of the casting is controlled to be approximately 4±1°C / s.
[0069] The metallographic structure of the Al-Si casting alloy obtained in Example 1 at 200X is as follows Figure 1 As shown. Figure 1 It can be seen that the microstructure of the cast aluminum alloy obtained in Example 1 is mainly composed of α-Al matrix, eutectic Si, Fe-containing phase, β-Mg2Si phase, Ce-containing phase, etc., among which the α-Al matrix is mainly dendritic and equiaxed.
[0070] The scanned images of the Al-Si casting alloy obtained in Example 1 at 1000X and 2500X are as follows: Figure 2 As shown, Figure 2 (b) includes the energy spectrum results. Figure 2 It can be seen that there is basically no obvious β-Al9Fe2Si2 phase in the scanning field of view of the cast aluminum alloy obtained in Example 1, and the Fe-containing phase becomes fine and evenly distributed, and there is no large-sized Fe phase. The energy spectrum results show that the Fe-containing phase is mainly π-Al 18 Fe2Mg7Si 10 It exists in the form of α-Al(Mn,Cr,Fe)Si, and also contains a small amount of Ce element, that is, Ce modifies the Fe phase and inhibits its growth; in addition, it also includes a bright white block phase, which is the Al4Ce3Si6 phase, and a small amount of β-Mg2Si phase.
[0071] Example 2
[0072] The Al-Si casting alloy has good corrosion resistance in the cast state, and the components of the Al-Si casting alloy are, by mass percentage, as follows: Si: 5.2wt%; Mg: 0.48wt%; Fe: 0.15wt%; Ti: 0.14wt%; Sr: 0.05wt%; Ce: 0.15wt%; Mn: 0.33wt%; Cr: 0.10wt%; Cu: 0.07wt%, and the rest are Al and unavoidable impurities.
[0073] The preparation method of the Al-Si casting alloy in this embodiment is the same as that in Embodiment 1.
[0074] Example 3
[0075] The Al-Si casting alloy has good corrosion resistance in the cast state, and the components of the Al-Si casting alloy are, by mass percentage, as follows: Si: 3.2wt%; Mg: 0.22wt%; Fe: 0.12wt%; Ti: 0.28wt%; Sr: 0.03wt%; Ce: 0.48wt%; Mn: 0.30wt%; Cr: 0.22wt%; Cu: 0.17wt%, and the rest are Al and unavoidable impurities.
[0076] The preparation method of the Al-Si casting alloy in this embodiment is the same as that in Embodiment 1.
[0077] Example 4
[0078] The Al-Si casting alloy has good corrosion resistance in the cast state. The composition of the Al-Si casting alloy, calculated by mass percentage, is: Si: 4.8wt%; Mg: 0.65wt%; Fe: 0.18wt%; Ti: 0.08wt%; Sr: 0.01wt%; La: 0.35wt%; Mn: 0.29wt%; Cr: 0.25wt%; Cu: 0.08wt%, and the rest is Al and unavoidable impurities.
[0079] The preparation method of the Al-Si casting alloy in this embodiment is the same as that in Embodiment 1, except that the raw material Al-Ce master alloy is replaced by Al-La master alloy.
[0080] Comparative Example 1
[0081] The difference between this comparative example and Example 1 is that no rare earth element is added to the raw materials for comparison, and the specific components of the Al-Si casting alloy are as follows by mass percentage: Si: 4.5wt%; Mg: 0.37wt%; Fe: 0.10wt%; Ti: 0.24wt%; Sr: 0.03wt%; Mn: 0.15wt%; Cr: 0.10wt%; Cu: 0.05wt%; the rest are Al and unavoidable impurities.
[0082] Comparative Example 2
[0083] The difference between this comparative example and Example 1 is that no trace elements of Mn and Cr are added for comparison, and the specific components of the Al-Si casting alloy are as follows by mass percentage: Si: 5.5wt%; Mg: 0.53wt%; Fe: 0.13wt%; Ti: 0.13wt%; Sr: 0.04wt%; Ce: 0.12wt%; Cu: 0.10wt%; and the rest are Al and unavoidable impurities.
[0084] Comparative Example 3
[0085] The difference between this comparative example and Example 1 is that no Cr trace element is added for comparison, and the specific components of the Al-Si casting alloy are calculated in percentage by mass: Si: 4.8wt%; Mg: 0.44wt%; Fe: 0.12wt%; Ti: 0.20wt%; Sr: 0.02wt%; Ce: 0.06wt%; Mn: 0.27wt%; Cu: 0.09wt%; and the rest are Al and unavoidable impurities.
[0086] Comparative Example 4
[0087] The difference between this comparative example and Example 1 is that no Mn trace element is added for comparison, and the specific components of the Al-Si casting alloy are calculated in percentage by mass: Si: 4.4wt%; Mg: 0.36wt%; Fe: 0.13wt%; Ti: 0.19wt%; Sr: 0.03wt%; Ce: 0.05wt%; Cr: 0.29wt%; Cu: 0.12wt%; and the rest are Al and unavoidable impurities.
[0088] Comparative Example 5
[0089] The difference between this comparative example and Example 1 is that no Sr trace element is added for comparison, and the specific components of the Al-Si casting alloy are calculated in percentage by mass: Si: 5.1wt%; Mg: 0.29wt%; Fe: 0.19wt%; Ti: 0.25wt%; Ce: 0.14wt%; Mn: 0.32wt%; Cr: 0.18wt%; Cu: 0.11wt%; the rest are Al and unavoidable impurities.
[0090] Comparative Example 6
[0091] The difference between this comparative example and Example 1 is that (Mn+Cr) / Fe>5 is selected for comparison, and the specific components of the Al-Si casting alloy are calculated in percentage by mass: Si: 5.3wt%; Mg: 0.31wt%; Fe: 0.12wt%; Ti: 0.21wt%; Sr: 0.02wt%; Ce: 0.13wt%; Mn: 0.40wt%; Cr: 0.29wt%; Cu: 0.15wt%; and the rest are Al and unavoidable impurities.
[0092] The specific examples and comparative examples are shown in Table 1:
[0093] Table 1 Main ingredients of Examples 1 to 4 and Comparative Examples 1 to 6 (wt%)
[0094] Group Si Mg Fe Ti Sr Ce La Mn Cr Cu (Mn+Cr) / Fe Example 1 4.6 0.34 0.08 0.22 0.02 0.05 - 0.10 0.09 0.06 2.4 Example 2 5.2 0.48 0.15 0.14 0.05 0.15 - 0.33 0.10 0.07 2.9 Example 3 3.2 0.22 0.12 0.28 0.03 0.48 - 0.30 0.22 0.17 4.3 Example 4 4.8 0.65 0.18 0.08 0.01 - 0.35 0.29 0.25 0.08 3.0 Comparative Example 1 4.5 0.37 0.10 0.24 0.03 - - 0.15 0.10 0.05 2.5 Comparative Example 2 5.5 0.53 0.13 0.13 0.04 0.12 - - - 0.10 0 Comparative Example 3 4.8 0.44 0.12 0.20 0.02 0.06 - 0.27 - 0.09 2.3 Comparative Example 4 4.4 0.36 0.13 0.19 0.03 0.05 - - 0.29 0.12 2.2 Comparative Example 5 5.1 0.29 0.19 0.25 - 0.14 - 0.32 0.18 0.11 2.6 Comparative Example 6 5.3 0.31 0.12 0.21 0.02 0.13 - 0.40 0.29 0.15 5.8
[0095] Performance Testing
[0096] (1) The microstructures of the Al-Si casting alloys prepared in Examples 1 to 4 and Comparative Examples 1 to 6 were quantitatively analyzed, and their grain sizes, eutectic Si proportions, Fe-containing phase types and sizes were calculated, as shown in Table 2.
[0097] Table 2 Microstructure characteristics of Al-Si casting alloys prepared in Examples 1 to 4 and Comparative Examples 1 to 6
[0098]
[0099] (2) The Al-Si casting alloys prepared in Examples 1 to 4 and Comparative Examples 1 to 6 were subjected to intergranular corrosion tests according to GB / T36174-2018. The test solution contained 30 g / L NaCl and 10 mL ± 1 mL of concentrated HCl (ρ = 1.19 g / mL). The solution temperature was 25 ° C. The samples were immersed in the solution for 24 h. The cross-sections of Examples 1, 2 and Comparative Examples 1, 2 after corrosion were observed as follows Figures 3 to 6 The maximum corrosion depth data of intergranular corrosion are shown in Table 3.
[0100] Table 3 Maximum corrosion depth of intergranular corrosion of Al-Si casting alloys prepared in Examples 1 to 4 and Comparative Examples 1 to 6
[0101]
[0102] Combined with Table 2, the addition of rare earth elements Ce / La forms new phases with Al and Si, promotes the nucleation of α-Al grains, and inhibits the growth of α-Al after nucleation, thereby achieving the purpose of grain refinement; on the other hand, rare earth Ce / La has a good modification effect on eutectic Si. Adding it together with Sr makes the modification effect of eutectic Si better and the particles smaller; in addition, rare earth Ce / La can be dissolved into the iron-containing phase ( Figure 2 ), changing the composition of the iron-containing phase, and at the same time, adsorbing on the tip of the iron-containing phase, hindering its growth, causing the tip of the iron-containing phase to be passivated and become fine. Therefore, in Comparative Example 1, there is no rare earth element effect, and the α-Al grains, eutectic Si, and Fe-containing phase of the alloy cannot be better refined, and the sizes are all large, which is not conducive to the formation of its oxide film, thereby deteriorating the corrosion resistance.
[0103] Since there is no trace amount of Mn, Cr and other elements in Comparative Example 2, the Fe phase types in the alloy are mainly β-Al9Fe2Si2 and π-Al 18 Fe2Mg7Si 10 phase, among which β-Al9Fe2Si2 has a very negative impact on the corrosion resistance of the alloy; while in Example 2, elements such as Mn and Cr are added in a coordinated manner to transform the β-Fe phase into the α-Al(Fe,Mn,Cr)Si phase which is closer to the matrix potential, and control the size of the α-Al(Fe,Mn,Cr)Si phase to avoid splitting the matrix, which is beneficial to improving the corrosion resistance of the alloy.
[0104] Comparative Examples 3 and 4 show that adding Mn alone can significantly reduce the β-Al9Fe2Si2 phase, but it cannot be added in large quantities and the improvement effect is limited; and adding Cr alone has no obvious effect on the conversion of β-Al9Fe2Si2, so it is necessary to add Mn and Cr elements in coordination to maximize the improvement of corrosion resistance.
[0105] Comparative Example 5 shows that in the alloy without Sr modification, the eutectic Si is only modified by rare earth Ce, the effect is weakened, the size is large, and it is not good for corrosion resistance. In Comparative Example 6, (Mn+Cr) / Fe is high, although β-Al9Fe2Si2 is greatly reduced, the size of α-Al(Fe,Mn,Cr)Si phase is increased, which still deteriorates the corrosion resistance.
[0106] Combined with Table 3, compared with the comparative example, the maximum corrosion depths of Examples 1 to 4 are reduced to varying degrees, indicating that their corrosion resistance is improved. This is because the modification of the rare earth Ce / La itself refines the alloy microstructure, including α-Al grain refinement, eutectic Si refinement, and Fe-rich phase refinement; at the same time, the modification of the Sr element on the eutectic Si makes it finer; and the synergistic addition of the Mn and Cr elements transforms the β-Fe phase in the structure that is very susceptible to corrosion into the α-Al(Fe,Mn,Cr)Si that is closer to the matrix potential and is not easily corroded.
[0107] Intergranular corrosion mainly occurs in the eutectic area, that is, the size and distribution of the α-Al matrix and eutectic Si play a decisive role in corrosion. As the grain size is refined, the grain boundary area is larger, which is conducive to increasing the formation rate of the alloy oxide film. At the same time, the small size of the eutectic Si and Fe phases greatly reduces the possibility of the oxide film being destroyed, and the oxide film is more complete and has fewer defects, thereby enhancing corrosion resistance. On the other hand, when the eutectic silicon is relatively small, its corrosion current is smaller and the corrosion rate is slowed down; the transformation of the β-Fe phase makes the Fe phase in the alloy mainly α-Al(Fe,Mn,Cr)Si and π-Al 18 Fe2Mg7Si 10 The potential difference between these two Fe phases and the matrix is relatively small, which reduces the probability of corrosion.
[0108] In summary, under the combined action of rare earth elements and trace elements such as Mn, Cr, Sr, etc., the corrosion resistance of the Al-Si casting alloy provided by the present invention in the cast state is improved.
[0109] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0110] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An Al-Si casting alloy having good corrosion resistance in the as-cast state, characterized in that: The chemical composition thereof includes, in percentage by mass, 3.0-5.5wt% Si, 0.2-0.8wt% Mg, ≤0.2wt% Fe, 0.03-0.3wt% Ti, 0.005-0.06wt% Sr, 0.02-0.5wt% RE, 0.05-0.4wt% Mn, 0.01-0.3wt% Cr, 0.05-0.2wt% Cu, and the rest Al and unavoidable impurities.
2. The Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 1, characterized in that: Among the element contents of the Al-Si casting alloy, the ratio of the sum of the contents of Mn and Cr to the content of Fe is 2-5.
3. The Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 1, characterized in that: The microstructure of the Al-Si casting alloy includes an α-Al matrix, a eutectic Si phase, a Fe-containing phase, a β-Mg2Si phase, and an Al4X3Si6 phase.
4. The Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 3, characterized in that: The α-Al matrix is dendritic and / or equiaxed, with an average grain size of 50 to 200 μm and a secondary dendrite arm spacing of 10 to 40 μm.
5. The Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 3, characterized in that: The volume fraction of the eutectic Si phase is 2-5%.
6. The Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 3, characterized in that: The eutectic Si phase is in the form of particles and fibers, and has an average size of 1 to 3 μm.
7. The Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 3, characterized in that: The Fe-containing phase includes α-Al(Fe, Mn, Cr)Si phase, π-Al 18 Fe2Mg7Si 10 phase, β-Al9Fe2Si2 phase.
8. The Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 3, characterized in that: The average size of the Fe-containing phase is 2 to 10 μm.
9. The Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 3, characterized in that: The total amount of the Fe-containing phase is less than 1.2 vol.%.
10. The Al-Si casting alloy with good corrosion resistance in the as-cast state according to claim 7, characterized in that: The content of the β-Al9Fe2Si2 phase is less than 0.05 vol.%.
11. The Al-Si casting alloy with good corrosion resistance in the as-cast state according to claim 3, characterized in that: The Al4X3Si6 phase includes Al4Ce3Si6 phase and / or Al4La3Si6 phase.
12. The Al-Si casting alloy with good corrosion resistance in the as-cast state according to claim 1, characterized in that: The RE is cerium, lanthanum or a combination of both.
13. A method for preparing the Al-Si casting alloy having good corrosion resistance in the as-cast state as claimed in any one of claims 1 to 12, characterized in that: The following steps are involved: Place pure Al ingot and Al-Si master alloy in a melting furnace and heat to 750-800°C for melting; The temperature of the smelting furnace is lowered to 740-780°C, Al-Ti master alloy, Al-Mn master alloy, Al-Cr master alloy, Al-RE master alloy and pure Cu agent are added into the smelting furnace for melting to obtain a melt, the melt is kept at 700-730°C, and then Mg blocks are added for melting and kept for a certain time; Then, the Al-Sr master alloy is added into a smelting furnace for melting to obtain a molten material; Then add 1.0-5.0‰ refining agent and 1.0-10.0‰ refiner of the mass of the molten material into the smelting furnace, stir and degas for 10-30 minutes, let it stand for 10-30 minutes, then slag and cast, and obtain Al-Si casting alloy with good corrosion resistance in the cast state.
14. The method for preparing the Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 13, characterized in that: The casting method includes gravity casting, high pressure casting, squeeze casting, low pressure casting or differential pressure casting.
15. The method for preparing the Al-Si casting alloy having good corrosion resistance in the as-cast state according to claim 13, characterized in that: During the casting process, the cooling rate of the casting is greater than or equal to 2℃ / s.